Aggression, Aggression-Related Psychopathologies and Their Models - Haller, József (Frontiers in Behavioral Neuroscience, 2022)
Neural mechanisms of aggression and violence are often studied in the laboratory by means of animal models. A multitude of such models were developed over the last decades, which, however, were rarely if ever compared systematically from a psychopathological perspective. By overviewing the main models, we show here that the classical ones exploited the natural tendency of animals to defend their territory, to fight for social rank, to defend themselves from imminent dangers and to defend their pups. All these forms of aggression are functional and adaptive; consequently, not necessarily appropriate for modeling non-natural states, e.g., aggression-related psychopathologies. A number of more psychopathology-oriented models were also developed over the last two decades, which were based on the etiological factors of aggression-related mental disorders. When animals were exposed to such factors, their aggressiveness suffered durable changes, which were deviant in the meaning that they broke the evolutionarily conserved rules that minimize the dangers associated with aggression. Changes in aggression were associated with a series of disfunctions that affected other domains of functioning, like with aggression-related disorders where aggression is just one of the symptoms. The comparative overview of such models suggests that while the approach still suffers from a series of deficits, they hold the important potential of extending our knowledge on aggression control over the pathological domain of this behavior.